2014
DOI: 10.1001/jamaneurol.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Value of18Fluorodeoxyglucose–Positron-Emission Tomography in Amyotrophic Lateral Sclerosis

Abstract: IMPORTANCE Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder primarily affecting the motor system, with extramotor involvement to a variable extent. Biomarkers for early differential diagnosis and prognosis are needed. An autosomal dominant hexanucleotide (GGGGCC) expansion in the noncoding region of the chromosome 9 open reading frame 72 (C9orf72) gene is the most frequent genetic cause of ALS, but its metabolic pattern has not been studied systematically.OBJECTIVES To evaluate the use of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
131
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(150 citation statements)
references
References 48 publications
10
131
0
1
Order By: Relevance
“…ALS, with both upper and lower motor neuron involvement, is part of the spectrum of motor neuron diseases consisting also of primary lateral sclerosis (PLS), with exclusively upper motor neuron disease, and progressive muscular atrophy (PMA), with only lower motor neuron disease. Both PMA and PLS can progress to ALS (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ALS, with both upper and lower motor neuron involvement, is part of the spectrum of motor neuron diseases consisting also of primary lateral sclerosis (PLS), with exclusively upper motor neuron disease, and progressive muscular atrophy (PMA), with only lower motor neuron disease. Both PMA and PLS can progress to ALS (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…In patients with ALS, a pattern of relative hypometabolism in the primary motor cortex, premotor cortices, and supplementary motor cortex but extending to extramotor areas such as the frontal and parietal lobes as well has been observed (2,4,(7)(8)(9)(10)(11). Relative hypermetabolism is observed in the mesotemporal cortex, cerebellum, and upper brain stem (2,4,7,10,(12)(13)(14). Within-center retrospective discriminant analysis methods to differentiate subjects with early ALS from controls have resulted in an overall classification accuracy of 90%-95% (2,4,10).…”
mentioning
confidence: 99%
“…Additionally, decreased metabolism was seen in the frontal brain regions. However, only the larger study reported decreased metabolism in the motor cortex [68]. A more recent study reported reduced metabolism in the frontal, motor, and occipital regions, and increased metabolism in the midbrain, temporal pole, and hippocampus in patients with ALS [69].…”
Section: Petmentioning
confidence: 91%
“…Two [ 18 F]FDG studies of patients with ALS reported increased metabolic activity in extramotor regions, including the upper brain stem, mesial temporal region, and cerebellum [67,68]. Additionally, decreased metabolism was seen in the frontal brain regions.…”
Section: Petmentioning
confidence: 99%
See 1 more Smart Citation